Amplifying consumers as partners in dissemination and implementation science and practice - Margaret E. Crane; Jonathan Purtle; Sara J. Becker (Implementation Research and Practice, 2023)
Background This Viewpoint argues for consumers (people with lived experience and their families) to be amplified as key partners in dissemination and implementation science and practice. Method We contend that consumer opinion and consumer demand can be harnessed to influence practitioners and policymakers. Results Amplifying consumers’ voices can improve the fit of evidence-based interventions to the intended end user. We offer recommendations of frameworks to engage consumers in the dissemination and implementation of health interventions. We discuss the primary types of evidence consumers may rely upon, including testimonials and lived experience. Conclusions Our intention is for this Viewpoint to continue the momentum in dissemination and implementation science and practice of engaging consumers in our work.